頌主心曲: 張多默聖樂作品集 - 張, 坤謀 (西安備修院, 2009)

奧地利布魯克納兒童合唱團 = Pequenos Cantores de S. Florino [Austria] = St. Florian Boy's Choir [Austria] (Instituto Cultural De Macau, 2008)

Ad te levavi animam meam: on the way to discovering Gregorian chant - Albarosa, Nino; Porfiri, Aurelio (Edition Music Contact, 2008)
OCLC: 500350621
Keywords: Chant grégorien; Chant grégorien Histoire; Gregorian chants; Gregorian chants History; History

「二十世紀初至今的澳門本土合唱作品」專輯發行演唱會 - Coro Perosi (Coro Perosi, 2008)
printed in macau

Voices of Prayer from Iberia: Renaissance & Baroque A Cappella Concert = 伊比利亞的禱聲: 文藝復興及巴羅克時期無伴奏合唱作品音樂會 - Ng, João (Coro Perosi, 2008)
printed in macau

跟隨羔羊2 = Suivre L' Asneau - Philippe, Marie-Dominique (天主教聞道出版社, 2008)
OCLC: 301930871
Keywords: Ji du tu; Tian zhu jiao ling xiu

Choral Sound 1: A Journal of Choral & Sacred Music - Porfiri, Aurelio (Macau Inter-University Institute, 2008)
2 copies; printed in macau

合唱經典: 歐洲文藝復興時期合唱曲選 - 戴, 定澄 (人民音樂出版社, 2008)
本書精選了歐洲文藝復興時期以來最經典, 最具代表性的宗教和世俗的複調合唱作品
OCLC: 430230573
Keywords: 合唱; 合唱 歌曲 欧洲 选集; 歌曲

澳門本土合唱作品演唱會 - Coro Perosi (Coro Perosi, 2007)
2 copies; printed in macau

《偉大的奧跡》文藝復興及巴羅克時期聖樂作品 = Obras Sacras Renascentistas e Barrocas "O Magnum Mysterium" - Coro Perosi, Perosi Choir (Coro Perosi, 2007)
printed in macau

嚶鳴合唱團成立十周年特刊 1997-2007 - Coro Perosi, Perosi Choir (Coro Perosi, 2007)
printed in macau

嚶鳴合唱團成立十周年特刊 1997-2007 - Coro Perosi, Perosi Choir (Coro Perosi, 2007)
printed in macau

培聖會三十周年暨司鐸年 - 聖樂欣賞晚會 - 劉, 偉傑 (澳門天主教培聖會, 2007)

音樂創作在澳門 = Music Composition in Macao - 戴, 定澄 (澳門日報出版社, 2007)
OCLC: 1268284567
Keywords: Composition (Music); Composition (Musique); Criticism; interpretation; etc; Music; Music History and criticism; Musique Histoire et critique; 作曲 (音樂); 音樂 澳門 歷史及評論

道成肉身: 聖若望福音第一章序言 - 江, 克滿; 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2007)
OCLC: 232192391
Keywords: Bible. John; I; 1-18; Catholic Church; Catholic Church Hymns; Hymns; Hymns; Chinese; Église catholique Hymnes

400 Years of Cultural Exchanges between China and Europe the History of the Grand Ricci Dictionary = 中歐文化交流400年《利氏漢法辭典》之溯源 (Ricci Institutes, 2006)
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries

Cambridge Latin Course: Book I (Cambridge University Press, 2006)
The leading Latin course worldwide Book I begins in the city of Pompeii shortly before the eruption of Vesuvius. Book I is full colour throughout, with a clear layout of stories and language notes. Featuring a glossary for quick reference and comprehension questions, the book also includes a full explanation of language points and grammar practice exercises
OCLC: 729656629
Keywords: Civilization; Latin (Langue) Étude et enseignement (Secondaire); Latin language Study and teaching (Secondary); Rome (Empire); Rome Civilisation; Rome Civilization

Last Minute English HKCEE For 2007 New Syllabus: The Essentials of The New Syllabus 5* - Eng, Richard (Original Press (Asia) Ltd., 2006)

Hong Kong Indult Tridentine Latin Mass: Solemn High Mass = 香港主教特准特倫多拉丁文彌撒 - Gounod, Charles (Rosary Church & Diocesan Liturgy Commission, 2006)

中英應用文大全 = A comprehensive guide to modern Chinese and English practical writing - 沈, 達信; 鄧, 彥龍 (世界出版社, 2006)
OCLC: 1296161366
Keywords: Letter writing; Letter writing; Chinese

Cambridge Latin Course: Book II (Cambridge University Press, 2005)
The leading Latin course worldwide
OCLC: 1312129990
Keywords: Civilization; Latin (Langue) Étude et enseignement (Secondaire); Latin language Study and teaching (Secondary); Rome (Empire); Rome Civilisation; Rome Civilization

Dicionário temático da lusofonia - Cristóvão, Fernando Alves; Amorim, Maria Adelina; Marques, Maria Lúcia Garcia; Moita, Susana Brites (ACLUS ; Texto Editores, 2005)
OCLC: 64220322
Keywords: Dicionários; Dictionaries; Geschichte; Kultur; Lusophonie Civilisation Dictionnaires portugais; Língua portuguesa; Portugais (Langue) Lusophonie Dictionnaires; Portugiesisches Sprachgebiet; Portuguese language; Portuguese language Portuguese-speaking countries Dictionaries; Portuguese-speaking countries; Portuguese-speaking countries Civilization Dictionaries Portuguese

Wheelocks Latin Grammar Fr. Anthony's Lectures on Wheelock's Latin - Father, Anthony (Catholic University College of Foreign Language & Literature, 2005)

Collins Latin dictionary (HarperCollins, 2005)
The Collins Latin Dictionary & Grammar offers the student of Latin the essential two-in-one reference: a comprehensive dictionary and a user-friendly grammar in one handy volume.
OCLC: 224371232
Keywords: Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language; Latin (Langue) Grammaire; Latin language; Latin language Grammar

區師達神父作品音樂會 = As Obras Do Pe. Áureo Castro - Ng, João (Coro Perosi, 2005)
printed in macau

Wheelock's Latin: [the classic introductory Latin course, based on ancient authors] - Wheelock, Frederic M.; LaFleur, Richard A. (Harper Collins, 2005)
OCLC: 435655508
Keywords: Civilization; Latin (Langue) Grammaire Problèmes et exercices; Latin language Grammar; Latin language Grammar Problems; exercises; etc; Problems and exercises; Rome (Empire); Rome Civilisation Problèmes et exercices; Rome Civilization Problems; exercises; etc

音樂表演在澳門—戴定澄音樂評論集 - 戴, 定澄 (澳門日報出版社, 2005)
printed in macau
Keywords: Analyse musicale; China Macau (Special Administrative Region); Concerts; Concerts China Macau (Special Administrative Region); Concerts Chine Macao; Criticism; interpretation; etc; Music; Music History and criticism; Music Performance; Music Performance China Macau (Special Administrative Region); Musical analysis; Musique Exécution Chine Macao; Musique Histoire et critique

慶祝林樂培八十大壽—聖樂合唱作品音樂會 = Concerto das Obras Corais Sacras em Honra do 80.º Aniversário de Doming Lam - Coro Perosi; Vanessa Leão, Maria; Ng, João (Coro Perosi, 2004)
printed in macau

English grammar for students of Latin: the study guide for those learning Latin - Goldman, Norma (Olivia and Hill Press, 2004)
Study guide for students of Latin. Explains grammatical terms in Latin and shows how they relate to English grammar. Review exercises with answers. Suitable for self-study, and developing grammar skills
OCLC: 57073642
Keywords: English language Grammar; Comparative Latin; Latin language Grammar; Comparative English; Latin language materials

牛津高階英漢雙解詞典, 第六版, 英漢雙解版 = Oxford advanced learner's English-Chinese dictionary, 6th ed. - Hornby, Albert Sydney; Wehmeier, Sally (Oxford University Press, 2004)
OCLC: 1293885968
Keywords: 1900-1999; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; English language; 英語 20 世紀 字典; 英語 20 世紀 字典 漢語; 英語 字典

靈頌 (時節篇) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2004)

O Salutaris (贖世羔羊) (Seminario de s. jose - Macau, 2003)
private print

Aurei Carmina: Choro - Castro, Áureo da Costa Nunes e (Dioecesis Macaonensis, 2003)
printed in macau
Keywords: Musical notation; Musique Notation

Aurei Carmina: Choro - Castro, Áureo da Costa Nunes e (Dioecesis Macaonensis, 2003)
printed in macau
Keywords: Musical notation; Musique Notation

靈頌 (禮儀常用經文) 伴奏譜(下) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2003)

靈頌 (聖父篇) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2003)

靈頌 (聖父篇) 伴奏譜 (上) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2003)

靈頌 (聖父篇) 伴奏譜 (下) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2003)

禮樂集26 - 蘇, 柏羲; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2003)

Story-Teller - Sepasitiano (Brother Sebastian, 2002)
4 copies

The Longing - Sepasitiano (Brother Sebastian, 2002)
2 copies

朗文中文新詞典: 詞典全文光盤 - 闕道隆; 李, 裕康 (培生教育出版亞洲有限公司, 2002)
OCLC: 264977416
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries

简明葡汉词典 = Dicionário conciso Portugue︢s︣-chine︢s︣ - 周汉军 (Commercial Press, 2002)
OCLC: 32612312
Keywords: Dicionários bilíngues; Dictionaries; Língua chinesa; Língua portuguesa; Portuguese language; Portuguese language Dictionaries Chinese

院聲歌集 - 李, 冠章 (天主教澳門教區, 2002)
非賣品; printed in macau

靈頌 (禮儀常用經文) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

靈頌 (禮儀常用經文) 伴奏譜(上) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

禮樂集22 - 蘇, 柏羲; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

禮樂集23 - 蘇, 柏羲; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

禮樂集24 - 蘇, 柏羲; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

禮樂集25 - 蘇, 柏羲; 蔡, 詩亞; 蘇, 柏羲 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2002)

Grand Dictionnaire Ricci de la Langue Chinoise = 利氏漢法辭典 Index2 et Concordance (Instituts Ricci (Paris-Taipei), 2001)
Keywords: Catholic Missions in Asia; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries

歐洲早期合唱曲精粹 - 戴, 定澄 (上海音樂出版社, 2001)
OCLC: 1268285790
Keywords: Choruses; Secular; Chœurs profanes; 大合唱世俗歌曲集

嚶鳴集3 - 林平良 (澳門崗頂前地聖奧斯定堂聖詠團, 2001)
printed in macau
Keywords: Catholic church Hymns; Hymns; Hymns; Chinese

靈頌 (聖母篇) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2001)

靈頌 (聖母篇) 伴奏譜 - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2001)

禮樂集21 - 蘇, 柏羲; 蔡, 詩亞; 陳, 永華 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2001)

禮樂集20 - 賈, 文亮; 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2001)

Aurei Carmina: Pianoforte et Organo - Castro, Áureo da Costa Nunes e (Dioecesis Macaonensis, 2000)
3 copies; printed in macau
Keywords: Musical notation; Musique Notation; Organ and piano music; Orgue et piano; Musique d'; Sonatas (Organ); Sonatas (Piano); Sonates (Orgue); Sonates (Piano)

Compendium of spirituality - Cea, Emeterio de; Aumann, Jordan (Alba House, 2000)
OCLC: 32241559
Keywords: Spirituality Catholic Church; Spiritualité Église catholique

The Melting Pot Gang - Sepasitiano (Brother Sebastian, 2000)
2 copies

感恩經 第三式 主禮及共制者用本 - 劉, 志明 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

[遠流] 活用英漢辭典 (遠流出版事業公司印行, 2000)
OCLC: 848316680

欧洲早期和声的观念与形态 - 戴定澄著. (上海音乐出版社, 2000)
2 copies
Keywords: Chuan tong he sheng yan jiu ou zhou; 传统和声 研究 欧洲

無師自通說英語: 情境英語口語現斈現用 = English for sixty occasions - 江瑞頴 (寂天文化, 2000)
OCLC: 1338327487
Keywords: 英國語言 會話

音樂與文學的對話 - 蒋, 理容 (揚智文化, 2000)
OCLC: 63204649
Keywords: Music appreciation; Musique Appréciation

Jubilaeum = 管樂五重奏 - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

靈頌 (短曲) - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

靈頌 (短曲) 伴奏譜 - 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

古典樂欣賞—人物篇 - 蔣, 理容 (揚智文化, 2000)
OCLC: 823026447
Keywords: Qi yue; Yin yue jia zhuan ji; Yue qi

古典樂欣賞—樂器篇 - 蔣, 理容 (揚智文化, 2000)
OCLC: 823026447
Keywords: Qi yue; Yin yue jia zhuan ji; Yue qi

禮樂集17 - 賈, 文亮; 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

禮樂集18 - 賈, 文亮; 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)

禮樂集19 - 賈, 文亮; 蔡, 詩亞 (Catholic Truth Society (公教真理學會) & 天主教香港教區聖樂委員會, 2000)